2022
DOI: 10.48550/arxiv.2202.09744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective spin model in momentum space: Toward a systematic understanding of multiple-$Q$ instability by momentum-resolved anisotropic exchange interactions

Abstract: Multiple-Q magnetic states, such as a skyrmion crystal, become a source of unusual transport phenomena and dynamics. Recent theoretical and experimental studies clarify that such multiple-Q states ubiquitously appear under different crystal structures in metals and insulators. Toward a systematic understanding of the formation of the multiple-Q states in various crystal systems, in this theoretical study, we present a low-energy effective spin model with anisotropic exchange interactions in momentum space. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

7
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 136 publications
(209 reference statements)
0
10
0
Order By: Relevance
“…Although the interactions between the further-neighboring spins play an important role in the RKKY system, only the out-of-plane DM interaction is present due to horizontal mirror symmetry under D 3h point group. The instabilities toward the SkXs based on a similar effective spin model with a particular set of the momentum-resolved interactions under other point groups have been investigated in both insulators [81,111,118,144,145] and metals [92,94,[104][105][106]110]. Hereafter, we set J = 1 as the energy unit and change D as a phenomenological parameter.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Although the interactions between the further-neighboring spins play an important role in the RKKY system, only the out-of-plane DM interaction is present due to horizontal mirror symmetry under D 3h point group. The instabilities toward the SkXs based on a similar effective spin model with a particular set of the momentum-resolved interactions under other point groups have been investigated in both insulators [81,111,118,144,145] and metals [92,94,[104][105][106]110]. Hereafter, we set J = 1 as the energy unit and change D as a phenomenological parameter.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Although the long-range nature of the interaction like the Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction [81,82,83] in itinerant magnets is different from the short-range one in frustrated insulating magnets, an effective multi-spin interaction arising from the Fermi surface instability gives rise to the groundstate SkX even without the DM interaction [78]. Similar to the frustrated magnets, it was shown that the effect of single-ion anisotropy [84,85,86,87], two-ion anisotropy [88,89,90,91,92,93], circularly polarized microwave field [94], and thermal fluctuations [95,96] enhance the stability of the SkX. It was also shown that the introduction of the DM or antisymmetric spin-orbit interaction in itinerant magnets leads to the SkX formation [43,97,98,99,100].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, magnetic anisotropy that arises from the rotational and mirror symmetry breakings in the specific lattice structures while keeping the inversion symmetry also becomes a source of the SkXs [79]. Although the form of the spin interactions depends on a way of breakings of the lattice symmetry, such an effect can appear in any discrete lattice systems via the spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 99%